Stable Expression of a Hepatitis E Virus (HEV) RNA Replicon in Two Mammalian Cell Lines to Assess Mechanism of Innate Immunity and Antiviral Response - Xu, Ling-Dong; Zhang, Fei; Peng, Lei; Luo, Wen-Ting; Chen, Chu; Xu, Pinglong; Huang, Yao-Wei (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) is one of the major etiological agents responsible for acute hepatitis. HEV does not replicate efficiently in mammalian cell cultures, thus a useful model that mimics persistent HEV replication is needed to dissect the molecular mechanism of pathogenesis. Here we report a genotype-3 HEV RNA replicon expressing an EGFP-Zeocin (EZ) resistant gene (p6-EZ) that persistently self-replicated in cell lines of human (Huh-7-S10-3) or hamster (BHK-21) origin after transfection with in vitro RNA transcripts and subsequent drug screening. Two cell lines, S10-3-EZ and BHK-21-EZ, stably expressed EGFP in the presence of Zeocin during continuous passages. Both genomic and subgenomic HEV RNAs and viral replicase proteins were stably expressed in persistent HEV replicon cells. The values of the cell models in antiviral testing, innate immune RNA sensing and type I IFN in host defense were further demonstrated. We revealed a role of RIG-I like receptor (RLR)-interferon regulatory factor 3 (IRF3) in host antiviral innate immune sensing during HEV replication. We further demonstrated that treatment with interferon (IFN-α) or ribavirin significantly reduced expression of replicon RNA in a dose-dependent manner. The availability of the models will greatly facilitate HEV-specific antiviral development, and delineate mechanisms of HEV replication.